Factors That Influence Consumer Satisfaction in Shopping Tourism at the Jakarta Traditional Clothing Market - Oktavia, Reno Catelya Dira; Gantina, Devita; Aditya, Michael Khrisna; Pramudito, Pramudito; Nasution, Deivy Zulyanti (Institut Pariwisata Trisakti, 2023)
The research aims to determine the influence of product quality, price, product variety, and online sales on consumer satisfaction on shopping trips at the Jakarta Traditional Clothing Market. This type of research is quantitative descriptive with multiple regression analysis methods. There are three research locations: Tanah Abang Market, Majestic Market, and Cipulir Market. Data were collected by distributing questionnaires with a Likert scale of 1 to 5; the sampling technique was purposive sampling. The sample in this study amounted to 150 people. Partial research results show that product quality, price, product variety, and online sales significantly affect consumer satisfaction. Good product quality can increase consumer satisfaction through appropriate design, materials, durability, and appearance, creating trust. Price plays a vital role in consumer satisfaction. Many consumers with a limited budget tend to feel satisfied with affordable prices because they get good value to influence the perception of product value. Product variety increases consumer satisfaction by providing more choices according to preferences and meeting various consumer style preferences. Online sales significantly impact consumer satisfaction, providing ease of shopping remotely, access to a wide selection of products, price comparisons, and easily customizable searches. Keywords: Product Quality, Price, Product Variety, Online Sales, Consumer Satisfaction